Analysis of the spatial distribution and dispersion of Plodia interpunctella (Lepidoptera: Pyralidae) in South Korea. (March 2020) - Lee, Wang-Hee; Jung, Jae-Min; Kim, Junggon; Lee, Hodan; Jung, Sunghoon
Abstract: This study proposes a novel method to predict the spatial dispersion of Plodia interpunctella by considering the climatic conditions and location of agricultural storage facilities. To accomplish the study objectives, a rearing experiment was conducted, and the CLIMEX model was used to evaluate the climatic suitability of P. interpunctella based on the model parameters estimated from the direct rearing experimental results, in addition to the previous rearing data. Subsequently, we evaluated the distances between the agricultural storage facilities [represented by rice processing complexes (RPCs) and agricultural product processing centers (APCs)] and main ports of grain entry by calculating the flight distance of P. interpunctella . As a result, the climate of South Korea was found unsuitable for P. interpunctella, but the suitability increased throughout the country when considering the indoor temperatures of storage facilities. The analysis of its dispersion with the consideration of grain entry ports, RPCs, and APCs showed that P. interpunctella could be dispersed to areas near storage facilities within 10 d by flying after its first introduction into the ports, as estimated by the calculated flight distance of 32.5 km. However, its dispersion could be accelerated by grain delivery and reach the farthest point in a day. This study provides a methodology to combine species distribution modeling with geographic information system, besides providing a possible scenario of P. interpunctella dispersion, which could serve as the fundamental data for establishing an adequate control strategy. Highlights: This study theoretically and experimentally investigated the spatial dispersion of P. interpunctella in South Korea. A method applicable for evaluating spatial dispersion of stored product insects was developed. CLIMEX model by internal temperature of agricultural facilities simulates the domestic distribution of P. interpunctella . Most of RPCs and APCs located within the flight distance of P. interpunctella suggests high potential for its dispersion.